Developing Assessment Specifications on the Basis of European Profiling Grid (Epg) Digital Media Enabling Competences for Undergraduate English Education Program - Neni Nurkhamidah (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
This research aims at developing assessment specifications on the basis of European Profiling Grid (EPG) digital media enabling competences for undergraduate English education program. The data used in this research are digital media enabling competence in the syllabi of five universities in Indonesia and digital media enabling competence in EPG document. This research applies Design and Development following the procedures adapted from Nunamakers (1991). To develop assessment specifications, two sub-questions are applied. Finding of the first question is three universities have independent course that equip students with digital media enabling competences. They also insert this competence in other courses. Two universities do not have this competence at all in their courses. Finding of the second sub-question shows that the level of similarity of digital media enabling competences in the existing syllabi and in EPG perspective is very low. The data of level the similarity of digital media enabling competences in the existing syllabi and in EPG perspective then used by researcher to develop assessment specifications. There are 15 item and 9 topics covered in this assessment specification. The assessment is in the form of performance assessment. Keywords: EGP, digital media enabling competences, test specification